Growth hormone secreting pituitary adenoma with admixed gangliocytoma and ganglioglioma. (September 2016) - Jukes, Alistair; Allan, Rodney; Rawson, Robert; Buckland, Michael E.
Highlights: Pituitary adenomas are usually derived from a single cell lineage. Collision tumours are two or more separate pathological entities mixed within the same sample. Gangliocytomas may promote the development of pituitary adenomas by hypersecretion of releasing hormones. Collision tumours may reflect aberrant migration of hypothalamic neurons. Abstract: Pituitary adenomas are the most common tumours found in the sellar region and, when both functioning and non-functioning adenomas are combined, account for 7–15% of primary brain tumours in adults. Rarely, admixed or discrete groups of cells comprising two or more tumour subtypes are seen; the so-called 'collision tumour'. We present a case of a 54-year-old-woman with a growth hormone-secreting pituitary adenoma admixed with both ganglioglioma and gangliocytoma. The possible mechanisms by which this may occur include a pre-existing gangliocytoma promoting the development of pituitary adenoma by hypersecretion of releasing hormones or aberrant migration of hypothalamic neurons in early embryogenesis.